Negativity as criteria for newsworthiness in Malaysian newspaper sports corpus - Kim, Hua Tan; Abdollahi-Guilani, Mohammad; Fatin Nazihah Ahamad Rusly, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study is an attempt to identify criteria for newsworthiness in Malaysian sports newspapers. It also seeks to find out how the media shapes the perception of Malaysians through sports news stories. Employing a corpus-based approach, with The Reuters Corpus Volume 1 and Malaysian English Sports News Corpus, the researchers of the study conducted a thematic analysis to look for recurring patterns that would detect the criteria for newsworthiness in the headlines and content of the corpus. It was found that football dominates the pages of the newspaper, and negativity, reference to elite people and nations are the most prominent news values. The patterns of language reveal a very negative sports world in which achievement and winning are stressed at all cost. Players and coaches are pressured to do well or they risk losing their jobs. Scandals are running rampant in the sports world as cases of corruption, drug abuse and bad behaviors among athletes and coaches are consistently reported in the news. Following McKane’s (2014) categorization of newsworthiness criteria, and using snowballing sampling method, 85 UKM students were asked to show their criteria for newsworthiness on a questionnaire, which resulted in a mismatch between the news stories and the readers’ expectations.